Relationship Between Sport Expertise and Postural Skills - Paillard, Thierry (Frontiers in Psychology, 2019)
The review adresses the relationship between sport expertise (i.e., sport competition level), postural performance (amount of motion of the centre of mass/of pressure of foot or ability to preserve body balance) and postural strategy (geometric organization of different body segments as well as neurobiological involvement of organism). Since the conditions of postural evaluation are likely to influence results, the aim is to compare athletes at different competition levels in ecological postural conditions (specific postural conditions related to the sport practiced) and non-ecological postural conditions (decontextualized postural conditions in relation to the sport practiced). Evidence suggests that the most successful athletes in terms of sport competition level have the best postural performance both in ecological and non-ecological postural conditions. However, in non-ecological conditions the postural tasks should be preferentially challenging or relatively close to the sport practice stance. Moreover, the most successful athletes also have more elaborate postural strategies compared with athletes at lower competition level. Mechanistic explanations as well as conceptual models are proposed to explain the role of different factors influencing the relationship between sport expertise and postural performance and strategy.